Вечный юноша. Проблема потенциала - Кравцов, А. С. (ХНУРЕ, 2020)
The article deals with archetype «Puer Aeternus». As the title implies the article describes main features of «eternal youths». A mention should be made examples of similar archetypes. The text gives valuable information on the potential of this archetype.
Keywords: философия; проблема потенциала